Tracheostomy in children: a ten-year experience from a tertiary center in southern Brazil, - Schweiger,Cláudia (2017)
Abstract Introduction: Children may require tracheostomy due to many different health conditions. Over the last 40 years, indications of tracheostomy have endorsed substantial modifications. Objective: To evaluate pediatric patients warranted tracheostomy at our Hospital, in regard to their indications, associated comorbidities, complications and decannulation rates. Methods: Retrospective study concerning patients under 18 years of age undergoing tracheostomy in a tertiary health care center, from January 2006 to November 2015. Results: 123 children required a tracheostomy after ENT evaluation during the study period. A proportion of 63% was male, and 56% was under one year of age. Glossoptosis was the most common indication (30%), followed by subglottic stenosis (16%) and pharyngomalacia (11%). The mortality rate was 31%. By the end of this review, 35 children (28.4%) had been decannulated, and the fewer the number of comorbidities, the greater the decannulation rate (0.77 ± 0.84 vs. 1.7 ± 1.00 comorbidities; p < 0.001). Conclusion: Tracheostomy in children is a relatively frequent procedure at our hospital. The most common indications are glossoptosis and subglottic stenosis. A high mortality rate was found, potentially substantiated by the high number of critical care patients with chronic neurological conditions in this cohort. Our decannulation rate is slightly below other series, probably because of the greater amount of patients with comorbidities.